Internal audit effectiveness in the Malaysian local authorities: internal auditors’ perspectives / Halimah @ Nasibah Ahmad - Ahmad, Halimah @ Nasibah (2013)
Similar to other public sector organizations, local authorities are facing increasing demand for governance and accountability. Hence, it was strongly recommended by various parties that it is necessary for all local authorities to have an effective internal audit function. Internal audit provides assistance to an organization in achieving its objectives through assessing and improving the effectiveness of risk management, control and governance processes. The main objective of this study is to investigate the influence of the internal and external organizational factors on the internal audit effectiveness in the Malaysian local authorities. Specifically, this study was conducted to investigate the influence of the human resource and administrative resource factors on the internal audit effectiveness. Moreover, this study also examines the moderating effects of the external factors (coordination with the external auditors and government support) on the internal audit effectiveness. In addressing the objectives of the study, the research framework draws on the integration of perspectives from two theories namely the resource-based theory and the institutional theory. There were 47 local authorities that have established internal audit departments/units when this study was carried out. The data collection process involved a mail survey addressed to all internal auditors in the 47 local authorities. The results of the study indicate that competency and professionalism have positive and significant relationship with the internal audit effectiveness. However, it was found that the quality of work performed, auditees’ attitude, top management support and interaction with the audit committee did not have significant influence on the internal audit effectiveness. With regards to the effects of the moderating variables on the relationships between the internal organizational factors and the internal audit effectiveness, results of the study showed that coordination with the external auditors moderated the relationships between professionalism, scope of service and the extent to which audit committee reviews the internal audit results and the internal audit effectiveness. Furthermore, findings of the study demonstrated that government support could moderate the relationships between professionalism, top management support and the extent to which the audit committee has reviewed the internal audit results and the internal audit effectiveness respectively.